Knowledge and practices of bush meat consumption among indigenous people in Belum Forest, Malaysia: an analytical cross-sectional study / Siti Fatimah Kader Maideen ... [et al.] - Kader Maideen, Siti Fatimah; Lau, Seng Fong; Rashid, Abdul; Hod, Rozita; Shafie, Intan Nur Fatiha (Faculty of Medicine, 2022)
Introduction: Orang Asli are the indigenous people of Peninsular Malaysia, and they consume bush meat as a primary source of protein. Frequent contact with wildlife through bush meat hunting for consumption and trade leaves people at risk of zoonotic infection. This study aims to assess the knowledge and practices of the Jahai tribe on the consumption and handling of bush meat. Methods: An analytical cross-sectional study was conducted among Jahai adults aged 18 years and above residing in Belum Forest. Due to their semi-nomadic nature of living, convenience sampling was used to select the participants, who were approached at their homes. A questionnaire was used to assess the knowledge and practices relating to bush meat and hygiene. Results: The majority of the participants ate bush meat regularly but had poor knowledge about disease transmission. There was a significant association between sex and occupation with knowledge. A significant association was found between knowledge on disease transmission with the consumption of bush meat. There was no association between practice on cooking, hunting activities and handling carcasses and hand hygiene practice with the consumption of bush meat. Conclusion: Most Jahai lacked sufficient knowledge on disease transmission and have poor practices regarding the handling of bush meat and its carcasses, which might put them at a risk of infection. The findings can be used as baseline data to develop effective strategies such as cultural-sensitive educational programs, to deepen the understanding of the community on the risk and prevention of developing diseases.